The Effectiveness of Quran Murottal Therapy in Reducing the Risk of Violent Behavior in Schizophrenia Patients at Panti Gramesia Cirebon - Ruswati, Ruswati; Trihandayani, Yani; Supriatin, Titin; Listiowati, Neni; Haritsah, Yolailah (Eastasouth Institute, 2025)
Schizophrenia is a chronic mental disorder that causes disturbances in thoughts, emotions, and behavior. According to WHO (2022), there are 24 million people with schizophrenia worldwide, with a prevalence in Indonesia of 1.8 per 1,000 population. At Panti Gramesia Cirebon, 24 patients were recorded to have a risk of violent behavior. To provide a real-life overview of nursing care for Mr. H, a schizophrenia patient with the nursing problem of risk of violent behavior. This study employed a case study design, with data collection through observation, interviews, and documentation. The subject was one patient at risk of violent behavior. Implementation was conducted for three days and showed improvement. Initially, the patient demonstrated strong violent impulses, such as making threats or self-harm. After interventions, the patient showed a significant reduction in violent urges, with better emotional control and reduced aggressive behavior. The combination of pharmacological therapy and non-pharmacological therapy (Quran Murottal Therapy) was effective in managing violent behavior. Collaboration between pharmacotherapy, nursing implementation strategies, and Quran Murottal Therapy proved effective in reducing aggression and symptoms of violent behavior risk.